PENGARUH GAME ONLINE TERHADAP MINAT BELAJAR SISWA KELAS VIII B1 SMP UNISMUH MAKASSAR - Muhammd Ari Wijaksana; Nasir (Almeera Education, 2022)
The formulation of the problem in this study is whether online games have an effect on student interest in SMP Unismuh Makassar. The purpose of this study is to determine whether online games have an effect on student interest in SMP Unismuh Makassar. This research is an Expofacto research. The population in this study were students of SMP Unismuh Makasaar totaling 294 with subjects 22 students of class VIII B1. Based on the results, showed that there was a significant effect of online games on the interest of students in class VIII B1 showed the average value (mean) of the X variable regarding the effect online game is89 which lies in the interval 83-95 with fairly high qualification. Meanwhile, the average value (mean) for the Y variable regarding student interest in class VIII B1 is on average of 29 which is located in the interval 29-31 with quite high qualifications.